The symbolic image of amaru in the colonial textual space: Nueva Corónica y Buen Gobierno and Comentarios Reales - Gonzales Muñoz, Francesca Ximena (2021)
This article proposes an approach to the symbolism of Amaru in order to analyze its representation in Nueva Corónica and Buen Gobierno by Guaman Poma de Ayala and Comentarios Reales by Inca Garcilaso de la Vega. In both texts the image of the snake appears to indicate the Andean-Western dichotomy, as well as one of the most common denominations, which was its translation into quechua “amaru”, considered as a representative symbol in artistic and archaeological sources during pre-Hispanic periods. and colonial. Its symbolic value is contextualized within medieval europe as a dragonscale figure and as an Andean idol that are gestated in oral traditions. Therefore, from the discursive analysis, the amaru is reinterpreted and acquires a semantic cultural density, reaffirming its importance as a symbol of the Andean and colonial tradition.